Critically ill obstetric patients - Bendre, Kirti Rajesh; Tuteja, Tanvi Vijay; Niyogi, Geeta Madhav (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objectives: To review all obstetric patients admitted in Intensive Care Unit (ICU) to access ethiology, required interventions, maternal mortality and to identify the conditions associated with maternal death. Methods: This is a retrospective study carried out in a medical college with tertiary hospital facility in Mumbai. The ICU admissions for a period of 5 years from October 2005 to October 2010 were reviewed. Results: Over 5 years, 48 out of 10800 obstetric patients were admitted in ICU (0.4%). Most common reasons for admissions were obstetric hemorrhage and preeclampsia. The most common intervention done was transfusion of blood and blood products. Conclusions: We need better information about high risk obstetrics in order to improve maternal care. The study identifies the risk factors for maternal mortality and severe maternal morbidity, most significant being obstetric hemorrhage. Lack of antenatal care and delay in referral to intensive care unit adversely affect the maternal outcome.